Ground eigenvalue and eigenfunction of a spin-weighted spheroidal wave equation in low frequencies - 唐文林 田贵花 (Chinese physics B, 2011)
Spin-weighted spheroidal wave functions play an important role in the study of the linear stability of rotating Kerr black holes and are studied by the perturbation method in supersymmetric quantum mechanics. Their analytic ground eigenvalues and eigenfunctions are obtained by means of a series in low frequency. The ground eigenvalue and eigenfunction for small complex frequencies are numerically determined.